Inovasi Model Problem Based Learning Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Prestasi Siswa di Era Digital - Mahmuda, Imaniar; Hafid; Munawaroh, Fitriatul (INCARE, International Journal of Educational Resources, 2025)
This study aims to analyze the innovation of the Problem-Based Learning (PBL) model in Islamic Religious Education as a strategy to improve student learning achievement in the digital era. The phenomenon behind this study is the low level of student engagement in conventional IRE learning and the need for a more contextual and adaptive learning model in line with developments in information technology. This research uses a qualitative approach with a library research method, through an in-depth analysis of various scientific literature, research articles, and relevant sources that discuss the application of PBL in the context of Islamic Religious Education. The results of the analysis show that the application of the PBL model in PAI learning encourages the development of critical thinking, problem solving, and collaboration Pendidikan Agama Islam in students through active engagement in authentic learning situations. Digital innovations such as the use of e-learning, interactive applications, and collaborative platforms strengthen the effectiveness of PBL by creating a flexible and participatory learning environment. These findings contribute to strengthening the PAI learning paradigm, which is not only oriented towards mastery of material, but also towards character building and 21st century competencies. In conclusion, PBL innovation in PAI learning has positive implications for improving academic achievement and developing students' religious values in the digital age. This study recommends the development of a technology-based PBL model and further research using an empirical approach to test its effectiveness in the context of learning at various levels of education